Numerical and Experimental Modeling of Flow Over a Broad-Crested Weir - Serdar Korkmaz; Nasir Ahmad Ghaznawi (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Broad-crested weirs arehydraulic structures installed in open-channels used to control the flow ofwater and measure the discharge. In this study, the flow over a broad-crestedweir in open-channel was experimentally and numerically modeled. Experimentswere carried out in a channel with a length of 1.5 m and a width of 0.055 munder five different flow rates. In each experiment, water depth and flow velocityin flow direction were measured using a pitot tube. Numerical model was developed using SimFlowsoftware. The velocities andpressure fields were computed numerically. The water depths and velocities in flow direction obtained from thenumerical model were compared to experimental values. There is generally a goodagreement between experimental and numerical results. Relatively small errorsin velocity profiles are observed in higher discharges.